2006
DOI: 10.1021/ja065794h
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Periodate-Mediated Cross-Linking of 3,4-Dihydroxylphenylalanine-Containing Molecules to Proteins

Abstract: Chemical cross-linking is an attractive approach to map peptide-protein and protein-protein complexes. Previously, we explored 3,4-dihydroxylphenylalanine (DOPA) as a protein cross-linking agent upon periodate oxidation.(Burdine, L.; Gillette, T. G.; Lin, H-J.; Kodadek, T. J. Am. Chem. Soc. 2004, 126, 11442-11443) We report here a study on the chemistry of DOPA-protein crosslinking. First, using a peptide nucleic acid (PNA) templated system, we identified the α-amino, ε-amino of Lys, imidazole of His, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
145
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(148 citation statements)
references
References 35 publications
3
145
0
Order By: Relevance
“…The results suggested that most receptors (ϳ90%) of the wild type and K269H mutant were crosslinked, whereas about 25 and 75% of the K269A and K269C receptors, respectively, were cross-linked. It has previously been reported that the periodate-activated DOPA system often results in high yields (30). The residual amount of crosslinking found in the wild-type receptor in the presence of ␣-factor (Fig.…”
Section: Volume 285 • Number 50 • December 10 2010mentioning
confidence: 80%
See 2 more Smart Citations
“…The results suggested that most receptors (ϳ90%) of the wild type and K269H mutant were crosslinked, whereas about 25 and 75% of the K269A and K269C receptors, respectively, were cross-linked. It has previously been reported that the periodate-activated DOPA system often results in high yields (30). The residual amount of crosslinking found in the wild-type receptor in the presence of ␣-factor (Fig.…”
Section: Volume 285 • Number 50 • December 10 2010mentioning
confidence: 80%
“…However, to efficiently couple to DOPA, the side groups of these amino acids and DOPA must be in very close proximity (30). Based on these findings, we investigated the cross-linking of Bio-DOPA 1 -␣-factor in Ste2p mutants K269A, K269C, and K269H that have lysine replaced with alanine, cysteine, and histidine, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we investigated the crosslinking potential of the DgHBPs with catechols using DgHBPpep. Sodium periodate (NaIO 4 ) was used to oxidize 4-methylcatechol (4MC) to the quinone form before crosslinking with deprotonated peptidyl His residues via Michael addition reactions 35 . Crosslinking was performed on both solution and coacervate forms of DgHBPpep (0.5 M ionic strength, pH 6 and 0.5 M ionic strength, pH 8, respectively) (Supplementary Fig.…”
Section: Crosslinking Of Dghbp-pep With 4-methylcatecholmentioning
confidence: 99%
“…28,29 If the pH of the swelling solution is increased above pK aI , the DOPA groups become ionized, and they are no longer hydrophobic. This result is most clearly observed for the DOPA40 gel.…”
Section: Hydrogel Formation and Characterizationmentioning
confidence: 99%